Islam and politics - Mandaville, Peter G., 1971- (New York : Routledge, 2014)
"Introduction to Islam and Politics"--
Previous edition published 2007 under title: Global political Islam.
Includes bibliographical references and index.
ESS
Keywords: Islam and politics; HISTORY / Middle East / General; POLITICAL SCIENCE / General